Diurnal patterns of salivary cortisol and DHEA using a novel collection device: Electronic monitoring confirms accurate recording of collection time using this device - Laudenslager, Mark L.; Calderone, Jacqueline; Philips, Sam; Natvig, Crystal; Carlson, Nichole E. (Psychoneuroendocrinology, 2013)
The accurate indication of saliva collection time is important for defining the diurnal decline in salivary cortisol as well as characterizing the cortisol awakening response. We tested a convenient and novel collection device for collecting saliva on strips of filter paper in a specially constructed booklet for determination of both cortisol and DHEA. In the present study, 31 healthy adults (mean age 43.5 years) collected saliva samples four times a day on three consecutive days using filter paper collection devices (Saliva Procurement and Integrated Testing (SPIT) booklet) which were maintained during the collection period in a large plastic bottle with an electronic monitoring cap. Subjects were asked to collect saliva samples at awakening, 30min after awakening, before lunch and 600min after awakening. The time of awakening and the time of collection before lunch were allowed to vary by each subjects’ schedule. A reliable relationship was observed between the time recorded by the subject directly on the booklet and the time recorded by electronic collection device (n=286 observations; r2=0.98). However, subjects did not consistently collect the saliva samples at the two specific times requested, 30 and 600min after awakening. Both cortisol and DHEA revealed diurnal declines. In spite of variance in collection times at 30min and 600min after awakening, the slope of the diurnal decline in both salivary cortisol and DHEA was similar when we compared collection tolerances of ±7.5 and ±15min for each steroid. These unique collection booklets proved to be a reliable method for recording collection times by subjects as well as for estimating diurnal salivary cortisol and DHEA patterns.